Three-Dimensional Technology in Rhinoplasty - De Greve, Glynnis; Malka, Ronit; Barnett, Erica; Robotti, Enrico; Haug, Martin; Hamilton, Grant; Lekakis, Garyfalia; Hellings, Peter William (Facial Plastic Surgery, 2022)
Rhinoplasty is uniquely suited to capitalize on different aspects of three-dimensional (3D) modeling technology. Currently, 3D surface imaging of preoperative and postoperative nasal structure provides a platform for better surgical planning and patient counselling as well as objective postoperative measurements. Physical nasal models using 3D printing technology can improve rhinoplasty performance intraoperatively, postoperative outcomes, together with nasal prosthetic manufacture, by tailoring to specific patient anatomy. Advances in tissue engineering using 3D-printed biocompatible scaffolds have shown excellent nasal cartilage mimicry and hold promise for increasingly versatile directed tissue regeneration in rhinoplasty and nasal reconstructive surgery. As health care innovations are expected to become increasingly common in standard rhinoplasty practices in the future, we give an account of how 3D technologies can create new opportunities to optimize surgical planning and improve overall the patient experience.
Keywords: rhinoplasty; 3D printing; tissue engineering; cone-beam computed tomography